Salazar contra "Superman" banda desenhada e censura durante o Estado Novo : o caso das publicações periódicas infanto-juvenis e o papel da Comissão Especial para Literatura Infantil e Juvenil e da Comissão da Literatura e Espectáculos para Menores (1950-1956) - Pinto, Ricardo Leite (História: revista da Faculdade de Letras da Universidade do Porto, 2017)
The study of Censorship of juvenile periodical publications during the "Estado Novo", practically ignored among us, will enlighten some lesser-known aspects of the history of the authoritarian regime previous to the 25th of April, especially in what regards the cultural and educational policies addressed to children, adolescents and young adults and the role of censorship in these policies. On another hand, it will also help to evaluate the reception and development in Portugal of "comics"as a paradigmatic phenomenon of "popular culture", which reached its peak during the 40s and 50s of the last century. This paper attempts to make a first approach to the subject, by studying the role of the "Comissão Especial para a Literatura Infantil e Juvenil" and the "Comissão da Literatura e Espectáculos para Menores" in the policing of some juvenile publications- "Mundo de Aventuras", "Cavaleiro Andante", "Titã", "Flecha" e "Valente" - between 1950 and 1956.